Allying interfacial engineering of 2D carbon nanosheet‐, graphene‐, and graphdiyne‐based heterostructured electrocatalysts toward hydrogen evolution and overall water splitting - Wuwei Mo; Joel Jie Foo; Wee‐Jun Ong (Electron)
Abstract Electrochemical hydrogen evolution reaction (HER) and overall water splitting (OWS) for renewable energy generation have recently become a highly promising and sustainable strategy to tackle energy crisis and global warming arising from our overreliance on fossil fuels. Previously, tremendous research breakthroughs have been made in 2D carbon‐based heterostructured electrocatalysts in this field. Such heterostructures are distinguished by their remarkable electrical conductivity, exposed active sites, and mechanical stability. Herein, with fundamental mechanisms of electrocatalytic OWS summarized, our review critically emphasized on state‐of‐the‐art 2D carbon nanosheet‐, graphene‐, and graphdiyne‐based heterostructured electrocatalysts in HER and OWS since 2018. Particularly, the three emerging carbonaceous substrates tend to be incorporated with metal carbides, phosphides, dichalcogenides, nitrides, oxides, nanoparticles, single atom catalysts, or layered double hydroxides. Meanwhile, fascinating structural engineering and facile synthesis strategies were also unraveled to establish the structure–activity relationship, which will enlighten future electrocatalyst developments toward ameliorated HER and OWS activities. Additionally, computational results from density functional theory simulations were highlighted as well to better comprehend the synergistic effects within the heterostructures. Finally, current stages and future recommendations of this brand‐new electrocatalyst type were concluded and discussed for advanced catalyst designs and future practical applications.